Efektivitas Mengunyah Buah Semangka (Citrullus Lanatus) Terhadap Penurunan Indeks Plak pada Remaja Desa Amud Mesjid Kabupaten Pidie - Rizqan Muzammina; Cut Aja Nuraskin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Background: Dental plaque is the primary cause of dental caries and periodontal disease. One natural approach to reducing plaque accumulation is the consumption of fiber-rich and water-rich fruits, such as watermelon (Citrullus lanatus). Objective: To determine the effectiveness of chewing watermelon (Citrullus lanatus) in reducing the plaque index among adolescents in Amud Mesjid Village, Pidie Regency. Methods: This study employed a quasi-experimental design using a one-group pre-test–post-test approach. A total of 52 adolescents were selected using a total sampling technique. Results: Before chewing watermelon, most respondents had a poor plaque index (54%). After the intervention, the majority of respondents had a good plaque index (56%). The Wilcoxon signed-rank test showed a statistically significant difference, with a p-value of 0.000 (p < 0.05). Conclusion: Chewing watermelon (Citrullus lanatus) is effective in reducing the plaque index among adolescents in Amud Mesjid Village, Pidie Regency.